The Role of DSN-MUI Fatwa in Indonesian Sharia Banking Development Flows in the Industrial Revolution 4.0 - Widayanti, Ipuk; Hiyun Puspita Sari, Silvia Waning (El-Qish: Journal of Islamic Economics, 2023)
The development of Islamic banking in recent years has experienced a very significant increase. This happens because it uses the principles of Sharia (Islamic law) and gets support from the government to accelerate Sharia banking activities. One form of support to improve the development of Islamic banking is the issuance of Law No. 21 of 2008 concerning Islamic Banking. An important authority in the dynamics of Sharia banking regulation is the National Sharia Council-Indonesian Ulema Council (DSN-MUI). This institution is an authoritative source in overseeing the obedience of Sharia banking industry players to comply with Sharia rules. The purpose of this study is to analyze the fatwa issued by the DSN-MUI on the development of Islamic financial institutions (LKS) in Indonesia, especially the Islamic banking sector. This study uses a qualitative method with a literature study approach. Findings: the results of this study conclude that the position of the DSN-MUI fatwa does not yet have a significant role in the development of Islamic bank products and services. This is because the fatwa acts only as a complement to Islamic bank products and services. In addition, the fatwa is a legal requirement for the Islamic banking sector in the context of Sharia compliance. The DSN-MUI fatwa is issued after the products and services have been published, not with a discussion mechanism first.